2021
DOI: 10.3389/fnins.2021.605654
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of N6 -Methyladenosine mRNA Methylation in a Rat Model of Cerebral Ischemia–Reperfusion Injury

Abstract: AimThis study was conducted in order to reveal the alterations in the N6-methyladenosine (m6A) modification profile of cerebral ischemia–reperfusion injury model rats.Materials and MethodsRats were used to establish the middle cerebral artery occlusion and reperfusion (MCAO/R) model. MeRIP-seq and RNA-seq were performed to identify differences in m6A methylation and gene expression. The expression of m6A methylation regulators was analyzed in three datasets and detected by quantitative real-time polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 53 publications
7
26
0
Order By: Relevance
“…Next, we determined whether the identified m 6 A peaks shared any common motifs. We found that m 6 A modifications were typically present in 5-RRACH-3 (R = A or G; H = A, C, or U) sequences ( Figure 3D ), as reported previously ( Yi et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Next, we determined whether the identified m 6 A peaks shared any common motifs. We found that m 6 A modifications were typically present in 5-RRACH-3 (R = A or G; H = A, C, or U) sequences ( Figure 3D ), as reported previously ( Yi et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
“…Among these, the most common internal modification in higher eukaryotes is m 6 A, which is important for mRNA metabolism and a variety of biological processes (Liu et al, 2018). m 6 A, discovered in the early 1970s, is a reversible and dynamic modification involving the methyltransferase complex (writer), demethylases (erasers), and binding proteins (readers) (Zhao Y. et al, 2021). Methyltransferase complexes, including methyltransferase-like 3 (METTL3), METTL14, and Wilms' tumor 1-associated protein (WTAP) (Lin et al, 2017), induce methylation, which can be reversed by fat mass and obesityassociated factor (FTO) and AlkB homologue 5 (ALKBH5) (Jia et al, 2011;Zheng et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that m6A modification increases in conditions like oxygen-glucose deprivation/reoxygenation (OGD/R) or middle cerebral artery occlusion and reperfusion (MCAO/R) ( Chokkalla et al, 2019 ). Researchers found that the demethylases (ALKBH5 and FTO) primarily contribute to causing abnormal m6A modification in IS ( Xu et al, 2020a ; Yi et al, 2021 ). Yi et al (2021) conducted a study in cerebral ischemia-reperfusion injury (CIRI) rat model to discover the variations in the m6A modifications and identified 1,160 differentially expressed genes having hypermethylated or hypomethylated m6A modifications.…”
Section: M6a Rna Methylation In Ischemic Strokementioning
confidence: 99%
“…Researchers found that the demethylases (ALKBH5 and FTO) primarily contribute to causing abnormal m6A modification in IS ( Xu et al, 2020a ; Yi et al, 2021 ). Yi et al (2021) conducted a study in cerebral ischemia-reperfusion injury (CIRI) rat model to discover the variations in the m6A modifications and identified 1,160 differentially expressed genes having hypermethylated or hypomethylated m6A modifications. The genes that showed differential expression due to hypermethylation were found to participate in inflammation-related processes, while genes with hypomethylation modification were found to be associated with the functioning of neurons and nerve synapses.…”
Section: M6a Rna Methylation In Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation